PENGARUH WAKTU PENYIMPANAN TERHADAP TINGKAT CEMARAN BAKTERI COLIFORM PADA MAKANAN TRADISIONAL LAWAR BALI - Ni Made Meri Sukmadhani; Nadya Kholifah; Putu Mutiara Ayu; I Nyoman Sujaya (Meditory : The Journal of Medical Laboratory, 2019)
Abstract. Lawar Bali is processed meat or minced vegetables that could occur contamination of bacteria in cultivation. Indonesian National Standart (SNI) 7388 in 2009 about maximum limit contamination of microbe in food, traditional food Lawar Bali included in processed meat product for contamination microbe APM Coliform that is 10/g. The aim of this research is to know influence of storage time towards contamination level of Coliform bacteria in traditional food Lawar Bali. This research is true experiment research (true experiment design) with posttest only control group design (control group with posttest) towards 25 units trial using five parameter time measurement that is zero hour, two hours, four hours, six hours and eight hours as much as five times repetition. Result of this research is showing that from 5 treatments influence storage time that given on 25 samples which is examined towards contamination level of Coliform bacteria in traditional food Lawar Bali there is reduction amount contamination Coliform bacteria in traditional food Lawar Bali each types of treatment in succession is on 0 hour with average about 178/gram, 2 hours with average 63/gram, 4 hours with average  19,4/gram, 6 hours with average 3,24/gram, and 8 hours with average 3,12/gram. Statistics analysis on Kruskal Wallis Test shows value sig 0,000(p0,05) so there is influence of storage time on contamination level Coliform bacteria in traditional food Lawar Bali. Conclusion of this research is there is influence of storage time towards contamination level Coliform bacteria in traditional food Lawar BaliKeywords : Storage Time, Coliform bacteria, Traditional food Lawar Bali